2018
DOI: 10.1080/00913847.2018.1482187
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of high-intensity exercise on hematological and iron metabolic parameters in elite male and female dragon boating athletes

Abstract: In conclusion, three consecutive high-intensity training bouts lead to elevated hepcidin levels and decreased iron levels in elite athletes of dragon boating. The increase in hepcidin levels may contribute to the risk of anemia in these athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…There were reductions in the plasma concentrations of Fe and Zn from baseline to the after of the incremental exercise to exhaustion. These results are in accord with recent studies indicating that the Fe stores were significantly decreased after exercise in men (18,(21)(22)(23)(24). In addition, the results are consistent with other studies which found the Zn reductions after exercise (25,34,35).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were reductions in the plasma concentrations of Fe and Zn from baseline to the after of the incremental exercise to exhaustion. These results are in accord with recent studies indicating that the Fe stores were significantly decreased after exercise in men (18,(21)(22)(23)(24). In addition, the results are consistent with other studies which found the Zn reductions after exercise (25,34,35).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, some studies have investigated the effects on Fe balance during short-term exercise. These studies clearly indicated that there is a significant decline in Fe stores in young men (18,(21)(22)(23)(24). There are some physiological functions required sufficient amounts of other minerals like Zn.…”
Section: Introductionmentioning
confidence: 91%
“…16,22,23 The consequences of this deficiency can take place in the short and long term, affecting appetite, immune response, learning capacity and neuropsychomotor development. [24][25][26] Thus, in athletes, anemia assumes clinical importance for both health and performance. 22,[24][25][26] According to Giudice et al, 27 in overweight/obesity, a lowgrade inflammation occurs in different tissues, and some studies have recently supported the idea that iron deficiency could be one of the comorbidities associated with the typical lowgrade inflammation in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Thus, in athletes, anemia assumes clinical importance for both health and performance. 22,[24][25][26] According to Giudice et al, 27 in overweight/obesity, a lowgrade inflammation occurs in different tissues, and some studies have recently supported the idea that iron deficiency could be one of the comorbidities associated with the typical lowgrade inflammation in obese patients. However, the results of our study did not confirm the association between overweight/ obesity and anemia in adolescent athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Untuk menghasilkan suatu prestasi yang lebih baik pada olahraga dayung Dragon boat diperlukan adanya latihan-latihan terutama latihan teknik mendayung dengan intensitas tinggi yang didalamnya terdapat beberapa aspek penting (Bauer et al, 2018;Brooke, 2015;Hsieh et al, 2012). Gerakan tepat yang diteliti secara biomekanik mampu menghasilkan kualitas gerak yang lebih efektif dan efisien (Hsieh & Knudson, 2018;Knudson, 2017;Warmenhoven et al, 2019) Oleh karena itu untuk mengetahui bagaimana gerakan teknik dan macam-macam komponen gerak dayung dragon boat secara biomekanika yang dimana komponen gerak tersebut terdiri dari posisi siap, posisi sudut kayuhan, dan kecepatan.…”
unclassified